Challenges students experience with inclusive education: Significance of listening and advocacy - Julien, Gabriel (Contemporary Research in Education and English Language Teaching, 2024)
Some experts, believe that the concept of inclusive education is still imprecise and nebulous and there is a nascent research and literature about this subject. When this non-empirical research was embarked upon there was no noticeable evidence to explicitly highlight that there is a meaningful understanding of the various challenges and obstacles that children face in inclusive education. Similarly, no evidence made the connection between inclusive education, listening, and advocacy. There is a gap due to the paucity of information and this research seeks to fill it. This author firmly believes that listening and advocacy are two major elements that enable and foster inclusion. Too often when policies are implemented those who are affected are not consulted. Educators and policymakers must pay more attention to the perspectives of children because they are quite capable of presenting their issues. In this way, inclusive education will be meaningful and cater to those who need it. This research analyzed and summarized recent published literature on the inclusion of children and the fieldwork is not novel. It is interesting to state, however, that research undoubtedly noted that there is a dearth of information that focuses on the various challenges that children encounter in inclusive education. It is crucial that everyone, especially professionals and policymakers, pay particular attention to the importance of inclusion. They also need to be cognizant of the experiences of these children and the role that advocacy plays, especially when they implement policies that relate to their growth and development.